Impact of CEO Characteristics on Corporate Tax Aggressiveness: Evidence from Listed Companies in Nigeria - Imam, Abduljalal Mukhtar (Curtin University, 2024)
This thesis, "Impact of CEO Characteristics on Corporate Tax Aggressiveness: Evidence from Listed Companies in Nigeria," explores how CEO attributes gender, nationality, tenure, educational background, and age statistically influence corporate tax strategies, while insider status shows no effect. Grounded in Upper Echelons and Agency Theories, secondary data from 92 non-financial firms (2018–2022) are analyzed. The findings highlight CEO characteristics' significant role alongside firm-specific factors like size and profitability, offering insights for corporate governance and tax policy compliance.